Randomized, Ascending Dose, Phase 2 Study of KHK4083, an Anti-OX40 Monoclonal Antibody, in Moderately Active Ulcerative Colitis. Issue 3 (9th June 2020) - Kierkus, Jaroslaw; Pesegova, Marina; Klopocka, Maria; Brankovic, Marija; Kasai, Noriyuki; Efuni, Sergey; Kong, Jennifer; Nakajima, Yu; Jordan, Christina; Matsui, Takeshi; Feagan, Brian G; Strout, Vincent
Abstract: Background: OX40 (CD134) plays a role in the maintenance of late T-cell proliferation and survival. KHK4083 is a monoclonal antibody directed against OX40. We aimed to assess the safety and preliminary efficacy of KHK4083 in patients with moderately active ulcerative colitis (UC). Methods: In this multicenter, double-blind, parallel-group, phase 2 study, patients with moderately active UC patients were randomized to ascending doses of intravenous KHK4083 (1, 3, or 10 mg/kg) or placebo every 2 weeks for 12 weeks. The primary endpoint was safety. The primary efficacy end point was the change from baseline in mean modified Mayo endoscopy subscore at week 12. Treatment with KHK4083 or placebo was continued every 4 weeks for up to 52 weeks in responders. Results: Long-term treatment with KHK4083 was well tolerated, with treatment-related adverse events being predominantly transient mild-to-moderate infusion-related reactions. Exploratory analysis of biopsy samples showed the virtually complete elimination of OX40+ cells in colon mucosa after 12 weeks of KHK4083 treatment. There were no significant differences between any of the randomized KHK4083 dose groups and placebo for the mean change in Mayo endoscopy subscore from baseline to week 12. Conclusions: KHK4083 can be safely administered intravenously at doses up to 10 mg/kg every 2 or 4 weeks for up to 52 weeks. Proof of pharmacodynamic action was confirmed by depletion of the elevated levels of the OX40+ cells associated with UC at all tested doses. Clinical response and mucosal healing (endoscopic improvement) in this population was not correlated with ablation of OX40+ T cells. Lay Summary: KHK4083, an anti-OX40 monoclonal antibody, investigated in a placebo-controlled, phase 2 clinical trial in ulcerative colitis patients proved safe but not effective when administered intravenously at up to 10 mg/kg every 2 or 4 weeks for up to 52 weeks.